Entre Ajuricaba(s) e Zumbi(s): currículo e diversidade cultural - a inclusão das temáticas culturais de matrizes indígenas e africanas na área de artes em escolas públicas da zona leste da cidade de São Paulo - Souza, Marinês Viana de (2010)
The cultural diversity in the Brazilian society has been an object of study over the last decades. In great part, it has put in evidence that the ideological construction of a harmonious multicultural scenario, from the point of view of the convenience between the different ethnic color racial groups is still considered a myth in the current days; considering that the same rights have not been given for these groups, and neither they have reached the same social, political, economical levels, nor their culture are equally acknowledged. The evidence of our cultural diversity has not blocked the spread of hegemonic cultural and artistic patterns, which reflected in the educational system and in the school curricula, and it has benefited that the Eurocentric vision of culture became a cultural reference in the curricular projects, in the detriment of a significant valorization and visibility of other cultural frameworks that forms our society, as the Indian and African ones. The inclusion of Afrobrazilian, African, and Indian history and culture teaching in the Brazilian Scholar Curriculum, determined by the Laws 10.639/03 and 11.645/08, has altered the Lei de Diretrizes e Bases da Educação Nacional number 9394/96. It represents, from the educational legislation point of view, the possibility to break with the exclusivity of the hegemonic canons of European culture that has, historically, pervading our school curriculum. The proposal for the teaching of these cultures according to these laws happens through thematics that should be approached in all school curriculum environments, do not characterizing into specific subjects. The present study is delimited in the Arts area and it proposes to investigate how the process of inclusion of cultural themes of African and Indian frameworks in the area of Arts teaching in public schools located in the East Zone in São Paulo has been developed. The participants of this research are the Arts teachers and the object of this study are the pedagogical practice developed and visualized in these professionals narratives, that reveal their knowledge and duties, their difficulties and possibilities, analyzed within a methodological approach of qualitative type, through the technique of content analyses. The theoretical contributions are placed in the confluence of three conceptual fields: Curriculum, Cultural Diversity, and Arts. It has been adopted authors referentials that approach the curriculum in a critical perspective, the cultural diversity from the optic of multicultural studies and the human rights, about Arts, approaching the relationship with teaching in schools